The peopling of Europe: a genetic perspective - Busby, GBJ (2012)
Following their dispersal out of Africa, humans colonised all continents of the world save one, Antarctica. Whilst Europe was initially peopled soon after this exodus, paleoclimatic, archaeological, and historical evidence suggest that successive waves and migrations of people have contributed to the population resident in Europe today. I therefore examined the impact of past events on the European population through the analysis of DNA sampled both from contemporary Europeans, and from worldwide populations pertinent to its history. I genotyped and analysed data from the Y chromosomes of over 2,000 haplogroup R-M269 European men from over 30 different populations and, in combination with comparable datasets gathered from the literature, show that there it is not possible to assign a date to the origin of this lineage in Europe, and thus that any conclusion as to the ancient or recent spread of this lineage in Europe is unfounded. I also show that commonly used Y chromosome lineage dating techniques based on STR variation are biased by the markers used and conclusions based on such dates should be viewed with a large amount of caution. I next use genome-wide SNP data from 1,550 individuals from 95 worldwide populations to explore the population structure of Europe and present an analysis of the detailed structure of Europe in a novel analytical framework using ChromoPainter and fineSTRUCTURE. Admixture analysis based this data reveals distinct genomic inputs to peripheral European populations, from North Africa, Sub-Saharan Africa, the Middle East, and East Asia, and provides dates for this admixture within the last 1,000 years that correspond to the emergence and decline of empires and kingdoms in these regions of Europe. This novel analysis highlights the importance of recent historical events on European population structure, but also suggests a degree of ancient structure across European populations. Taken together, these analyses demonstrate the substantial effects of both ancient and recent migrations and mixture on the contemporary genetic structure of Europe.